Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acssynbio.6b00064
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication in Engineered Escherichia coli Genomes with Extra Replication Origins

Abstract: The standard outline of bacterial genomes is a single circular chromosome with a single replication origin. From the bioengineering perspective, it appears attractive to extend this basic setup. Bacteria with split chromosomes or multiple replication origins have been successfully constructed in the last few years. The characteristics of these engineered strains will largely depend on the respective DNA replication patterns. However, the DNA replication has not been investigated systematically in engineered ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
(125 reference statements)
0
22
0
Order By: Relevance
“…The integration of a plasmid-derived origin that could be induced with IPTG at a location ∼450 kb away from oriC was successful, but if this origin was active, it repressed activity of oriC (Kouzminova and Kuzminov, 2008). In another study, integration of a shorter oriC fragment in two chromosomal locations, one roughly equivalent to the oriZ position while the second was closer to the termination area (1.6 Mbp), did not result in any detectable initiation at the ectopic origins (Milbredt et al, 2016). The authors suggested that origin activity might be influenced by the presence of flanking genes (Milbredt et al, 2016), which would explain why the longer 5 kb oriC region stretch developed in the Sherratt lab (Wang et al, 2011) proved active.…”
Section: Introducing a Second Origin Into The E Coli Chromosomementioning
confidence: 96%
See 1 more Smart Citation
“…The integration of a plasmid-derived origin that could be induced with IPTG at a location ∼450 kb away from oriC was successful, but if this origin was active, it repressed activity of oriC (Kouzminova and Kuzminov, 2008). In another study, integration of a shorter oriC fragment in two chromosomal locations, one roughly equivalent to the oriZ position while the second was closer to the termination area (1.6 Mbp), did not result in any detectable initiation at the ectopic origins (Milbredt et al, 2016). The authors suggested that origin activity might be influenced by the presence of flanking genes (Milbredt et al, 2016), which would explain why the longer 5 kb oriC region stretch developed in the Sherratt lab (Wang et al, 2011) proved active.…”
Section: Introducing a Second Origin Into The E Coli Chromosomementioning
confidence: 96%
“…In another study, integration of a shorter oriC fragment in two chromosomal locations, one roughly equivalent to the oriZ position while the second was closer to the termination area (1.6 Mbp), did not result in any detectable initiation at the ectopic origins (Milbredt et al, 2016). The authors suggested that origin activity might be influenced by the presence of flanking genes (Milbredt et al, 2016), which would explain why the longer 5 kb oriC region stretch developed in the Sherratt lab (Wang et al, 2011) proved active. However, our attempts to integrate the same 5 kb oriC fragment into the malT gene at 76.5 min, approximately 1/4 into the left-hand replichore, to generate oriC + oriY + cells ( Figure 2C), proved unsuccessful.…”
Section: Introducing a Second Origin Into The E Coli Chromosomementioning
confidence: 98%
“…Spreading the genetic information to multiple replicons might actually have considerable benefits (Liang et al, 2013; Schindler and Waldminghaus, 2015; Milbredt et al, 2016). Since using the replication origin of the V. cholerae secondary chromosome as basis for a synthetic secondary chromosome in E. coli has proven a suitable approach, we set out to probe the origin diversity of the Vibrio genus for its potential as third chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…One interesting alternative is the replication origin of the secondary chromosome of Vibrio cholerae . This origin has been shown to replicate in Escherichia coli and was used in several respective genome engineering projects (Egan and Waldor, 2003; Liang et al, 2013; Messerschmidt et al, 2015; Milbredt et al, 2016; Zhou et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Measuring the whole-cell fluorescence can be performed precisely and in high throughput by flow cytometry on a single-cell level. This would be a great advance compared to conventional copy number measurements, such as quantitative PCR or marker frequency analysis by microarrays or next-generation sequencing (Milbredt et al 2016; Skovgaard et al 2011; Stokke et al 2011). In our experiments, fluorescence intensities of cells with two copies of the OL1/UAS hybrid FROS array were higher than cells with only a single copy (Figure 6).…”
Section: Discussionmentioning
confidence: 99%